Radiation effects in astrophysical ices. (June 2015) - Boduch, Philippe; Dartois, Emmanuel; de Barros, Ana L F; da Silveira, Enio F; Domaracka, Alicja; Lv, Xue-Yang; Palumbo, Maria Elisabetta; Pilling, Sergio; Rothard, Hermann; Duarte, Eduardo Seperuelo; Strazzulla, Giovanni
Abstract: The interaction of heavy ions with astrophysical ices was studied at different beamlines of GANIL by infrared absorption spectroscopy. This allowed simulating in the laboratory the physico-chemical modifications induced in icy objects in space, exposed to radiation fields such as the solar wind, magnetospheric particles and interstellar cosmic rays. We briefly discuss sputtering, destruction and formation of molecules, amorphization and compaction, implantation, and finally the formation of organic molecules. This latter topic is related to the question of the initial conditions for the emergence of life.